Hot origin of the Little Bang - Akkelin, Sergii V. (The European physical journal. A, Hadrons and nuclei, 2017)
Ultrarelativistic heavy ion collisions produce a quark-gluon matter which lies in the future light cone originating from given points on the t = z = 0 plane of the Minkowski spacetime manifold. We show that in a weak coupling regime the Minkowski vacuum of massless fields presents itself in the “Little Bang” region as a thermal state of low pTpT p_{T} particles, in close analogy to the Unruh effect for uniformly accelerated observers which are causally restricted to a Rindler wedge. It can shed some light on the mechanisms of early time thermalization in ultrarelativistic heavy ion collisions.
Gesehen am 12.04.2018